2010
DOI: 10.1097/rhu.0b013e3181c78856
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in World Trade Center Rescue Workers Presenting With Rheumatologic Manifestations

Abstract: The health consequences of the World Trade Center collapse are unknown, but likely to be significant and may take years to fully appreciate. Sarcoidosis is a multisystem inflammatory disorder of unknown etiology characterized pathologically by noncaseating granulomas. Inciting events, such as infectious agents or possible environmental exposures, have been postulated as the source of antigen exposure initiating an inflammatory cascade. We describe 2 cases of sarcoidosis in rescue workers with significant expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Bowers et al (2010) examined health consequences of the WTC collapse in terms of incident sarcoidosis, a multisystem inflammatory disorder of unknown etiology characterized pathologically by non-caseating granulomas. They described two cases of sarcoidosis in rescue workers with significant exposure from the WTC collapse and who presented with extrapulmonary rheumatologic manifestations.…”
Section: Groups With Results Based On Clinical Observationsmentioning
confidence: 99%
“…Bowers et al (2010) examined health consequences of the WTC collapse in terms of incident sarcoidosis, a multisystem inflammatory disorder of unknown etiology characterized pathologically by non-caseating granulomas. They described two cases of sarcoidosis in rescue workers with significant exposure from the WTC collapse and who presented with extrapulmonary rheumatologic manifestations.…”
Section: Groups With Results Based On Clinical Observationsmentioning
confidence: 99%
“…The lay press has also reported four case fatalities due to interstitial pulmonary fibrosis, sarcoidosis (cardiopulmonary involvement) and granulomatous pneumonitis in non-FDNY subjects who were exposed to the WTC dust [Izbicki et al, 2007]. Additionally, sarcoidosis with extrapulmonary rheumatologic manifestations was also reported in two New York City police officers following exposure to pollutants during their rescue operations at Ground zero [Bowers et al, 2010].…”
Section: Introductionmentioning
confidence: 93%
“…They stratified individuals in their cohort based on self-reported dust cloud exposures and observed that more intensive rescue and recovery activities were associated with increased disease risk [10]. Some such cases of World Trade Center sarcoidosis-like illness demonstrate extensive, multiorgan involvement [11]. Additionally, Crowley and coworkers calculated an extraordinarily high annual incidence rate of 229 sarcoidosis cases per 100,000 person years, based on record review of nearly 20,000 individuals in their World Trade Center medical surveillance program [12], providing independent confirmation of what had previously been published in a cohort of New York City firefighters and emergency response personnel.…”
Section: Contribution Of Inorganic Particulates To Sarcoidosis Riskmentioning
confidence: 99%